DETERMINAN KEPEMILIKAN ASING, KEPEMILIKAN MANAJERIAL, KEBIJAKAN HUTANG, DAN KEBIJAKAN DIVIDEN TERHADAP KINERJA KEUANGAN - Esthie Nur W.A; Mukhzarudfa Mukhzarudfa; Yudi Yudi (Jurnal Akuntansi & Keuangan Unja, 2021)
The purpose of this research is the determine the effect of managerial ownership, foreign ownership, debt policy and dividend policy on financial performance in state-owned companies in Indonesia. This research is a case study with the research population being all state-owned companies. Based on data released by BUMN (bumn.go.id), in 2018 there were 115 BUMN companies. Meanwhile, the sample that met the purposive sampling criteria was 16 companies. This research is a quantitative study and uses secondary data from the annual report. The method used in this research is multiple linear regression analysis with the help of the SPSS 23 program. The results show that simultaneously with managerial ownership, foreign ownership, debt policy, and dividend policy have a positive effect on the independent variable of financial performance. Managerial ownership variable does not have a positive effect on financial performance. The foreign ownership variable has no positive effect on financial performance. The debt policy variable has a negative effect on financial performance. Dividend policy variable has a positive effect on financial performance.